Role of Toll‐like Receptors 2 and 4 in Mediating Endothelial Dysfunction and Arterial Remodeling in Primary Arterial Antiphospholipid Syndrome1. Issue 11 (November 2014) - Benhamou, Ygal; Bellien, Jeremy; Armengol, Guillaume; Brakenhielm, Ebba; Adriouch, Sahil; Iacob, Michele; Remy‐Jouet, Isabelle; Le Cam‐Duchez, Véronique; Monteil, Christelle; Renet, Sylvanie; Jouen, Fabienne; Drouot, Laurent; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the role of Toll‐like receptors (TLRs) in antiphospholipid antibody (aPL)–mediated vascular abnormalities in patients with primary arterial antiphospholipid syndrome (APS). Methods Forty‐eight subjects participated in the study. Arterial function and structure and TLR pathway activation were determined in patients with primary arterial APS and matched controls. The pathogenic effects of aPL isolated from patients were assessed in wild‐type (WT) and TLR‐knockout mice. Results APS patients had endothelial dysfunction, arterial stiffening, and hypertrophy, as evidenced by decreased brachial artery endothelium‐dependent flow‐mediated dilation (FMD) and increased aortic pulse wave velocity and carotid intima‐media thickness (IMT), as compared with controls. Plasma samples from APS patients revealed decreased nitric oxide (NO) availability and a pro‐oxidative, proinflammatory, and prothrombotic state illustrated by a decrease in nitrite and an increase in lipid peroxidation, tumor necrosis factor α levels, and tissue factor (TF) levels. Furthermore, TLR pathway activation was found in APS patients with increased TLR‐2 and TLR‐4 messenger RNA expression and increased protein levels of the activated TLR transduction protein interleukin‐1 receptor–associated kinase 1 in peripheral blood mononuclear cells. Moreover, agonist‐stimulated cell‐surface expression of TLR‐2 and TLR‐4 in circulating monocytes was higher in APS patients than in controls. These changes were positively associated with IMT and negatively associated with FMD. Finally, aPL injection decreased mesenteric endothelium‐dependent relaxation and increased TF expression in WT mice but not in TLR‐2– or TLR‐4–knockout mice. Conclusion This translational study supports the notion that TLR‐2 and TLR‐4 play a role in mediating vascular abnormalities in patients with primary arterial APS. TLRs thus constitute a promising pharmacologic target for preventing cardiovascular complications in APS.